Towards a green economy - Hepburn, Cameron (Henry Stewart Talks, 2019)
The Anthropocene, Sustainable development, Natural capital, Resource limitations, Declining biodiversity, Global warming, The economy and the biosphere, Renewable energy prices, Carbon prices, Efforts to combat climate change